Extraction of α‐neurotoxins from equine plasma by receptor based affinity purification. Issue 7 (13th April 2020) - Timms, Mark; Ganio, Katherine; Steel, Rohan
Abstract: Venoms were first identified as potential doping agents by the racing industry in 2007 when three vials of cobra venom were seized during an inspection of a stable at Keeneland Racecourse in the USA. Venoms are a complex mixture of proteins, peptides, and other substances with a wide range of biological effects, including inhibiting the transmission of nervous and muscular impulses. As an example of this, cobratoxin, an α‐neurotoxin found in cobra venom, is claimed to be an effective treatment for pain. Recent analysis of seized samples identified venom from two different species of snake. Proteomic analysis identified the first sample as cobra venom, while the second sample, in a vial labeled "Conotoxin", was identified as venom from a many banded krait. Cobratoxin, conotoxins, and bungarotoxins (a component of krait venom) are all α‐neurotoxins, suggesting a common application for all three venom proteins as potential pain blocking medications. Using a peptide based on the nicotinic acetylcholine receptor, a one‐step affinity purification method was developed for the detection of α‐neurotoxins in plasma. Abstract : Alpha‐neurotoxins from the many banded krait, the monocled cobra, and the cone snail Conus vexillum were extracted from equine plasma using a receptor based affinity purification strategy and identified by LCMSMS with confirmation down to 0.6 ng/mL.